Effects of Seasonal Precipitation on the Amount of Seepage-A Case Study of Tunnel 3 of Bazai Irrigation Project Khyber Pakhtunkhwa - Ullah, Arshad; Alam, M Mahboob; Mat Said, K N; Kassim, A; Abbil, A; Alam, I (International Journal of Integrated Engineering, 2022)
Infiltration of water into tunnel within a harsh geological formation is a vital issue in tunnelling. The consequence impacts due to seepage include tunnel rock instability, pore-water pressure imposition and diminution of operational capacity. The spatial variation in rainfall due to climate change intensifies the threat to tunnel stability. Likewise, to understand the impacts of climate change scenarios on the seepage of tunnel 3 of the Bazai irrigation project was numerically simulated in SEEP/W software by manipulating the rainfall data. The net annual precipitation is followed by two sets of rainfall data i.e., dry and wet season precipitation depending upon the magnitude of rainfall. The analysis revealed that most of the seepage occurred in the unlined portion. In order to determine the future impacts of precipitation on seepage quantity, the wet season precipitation was further increased by 10% and 50% for A1B and B2 conditions respectively. The seepage quantity into the tunnel increases with variation in precipitation patterns. To reduce the risk to tunnel stability, the model was also treated with cement-bentonite grout and bentonite slurry containing 6% solids. The performance of both grouting techniques leads to noticeable seepage deduction. The study further suggests that cement-bentonite is more effective in seepage remediation.